2017
DOI: 10.1038/tp.2016.280
|View full text |Cite
|
Sign up to set email alerts
|

Particulate air pollutants, APOE alleles and their contributions to cognitive impairment in older women and to amyloidogenesis in experimental models

Abstract: Exposure to particulate matter (PM) in the ambient air and its interactions with APOE alleles may contribute to the acceleration of brain aging and the pathogenesis of Alzheimer's disease (AD). Neurodegenerative effects of particulate air pollutants were examined in a US-wide cohort of older women from the Women's Health Initiative Memory Study (WHIMS) and in experimental mouse models. Residing in places with fine PM exceeding EPA standards increased the risks for global cognitive decline and all-cause dementi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
300
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 343 publications
(315 citation statements)
references
References 58 publications
14
300
0
1
Order By: Relevance
“…In addition, results of this study showed a strong relationship between traffic-related air pollution and child's attention within long-term contact with air pollution compared to short-term contact [4]. Another study was conducted by M Cacciottolo and his colleagues under the title of "particulate air pollutants, APOE alleles and their contributions to cognitive impairment in older women and to amyloidogenesis in experimental models" [5]. Authors of this research have expressed that exposure to air particulates (PM) and its interaction with APOE alleles may contribute to aging brain and Pathogenesis of Alzheimer's Disease (AD).…”
Section: Researches Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…In addition, results of this study showed a strong relationship between traffic-related air pollution and child's attention within long-term contact with air pollution compared to short-term contact [4]. Another study was conducted by M Cacciottolo and his colleagues under the title of "particulate air pollutants, APOE alleles and their contributions to cognitive impairment in older women and to amyloidogenesis in experimental models" [5]. Authors of this research have expressed that exposure to air particulates (PM) and its interaction with APOE alleles may contribute to aging brain and Pathogenesis of Alzheimer's Disease (AD).…”
Section: Researches Resultsmentioning
confidence: 62%
“…Results obtained from this study showed that living in places consisting of PM levels higher than EPA standards increases the risk of cognitive disorder and dementia equal to 81% and 92%, respectively so that such pollution has destructive effects on AP-OE 4.4 carriers. Infrastructural mechanisms may include increased brain Aβ production and changed CA1 hippocampal neurons and glutamate receptor subunits [5]. Another study was conducted by Jeanette A.Stingone and colleagues under the title of "using machine learning to identify air pollution exposure profiles associated with early cognitive skills among U.S. children"; this study was conducted in medical department of social health and environment in Sinai School of Medicine in New york [6].…”
Section: Researches Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A mechanistic basis for the effects of PM may be translocation of particles to the brain. 75,[84][85][86] Interestingly, cognitive decits due to air pollution were suggested around the year 1200, when the philosopher Maimonides attributed "dullness of understanding, failure of intelligence and defect of memory" to air pollution.…”
mentioning
confidence: 99%